A Dissect Of Gender Analysis With Components Of Customer Engagement In Regard To Green Concept Within Retailing Sector - Reference To Kanniyakumari District (International Journal of Food and Nutritional Sciences, 2022)
This research is directed at identifying the gender gap towards the factors of customer engagement in green practices which play a vital role in retaining the customer towards the business. In recent years having sustainable end users in the sustainable and competitive market is a laborious task. Due to the drastic change in the environment that impacts the Awareness level among final users about to go green. So, the emerging green concept has a huge impact on Customer engagement in the retailing sector. This exploration recognizes the outlook of gender towards customer engagement factors like physical aspect, Approachability, Trustability, Awareness, product, publicity, Responsibility, price, customer Commitment, and CRM practices. This study is conducted among the gender(customer) from various retail outlets where the green practices are in boom. And the result of this study reveals the role of customer engagement among gender and its factors which play a pivotal role in green evolution in the upcoming market scenario.